PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI STRATEGI PEMBELAJARAN QUANTUM TEACHING SISWA KELAS VI SD NEGERI 173321 PARANGINAN - Jainal B Togatorop; Eddi S Togatorop (JURNAL CURERE, 2018)
This study aims to investigate the implementation of learning and improving student learning outcomes. Implementation of the research conducted in two cycles. Subjects in the study of six graders, totaling 28 students.From the results of data analysis, has obtained an increase in teacher activity observation results with the percentage of 67.27% and a percentage increase of 75.55% student activity which is included in both categories. The completeness of student learning outcomes individually on the second cycle increased to 22 students with a percentage of 89.65% and the average value of students also increased from 66.98% to 76.72%. Based on the research results, the obtained improving student learning outcomes after using "Quantum teaching" in the subjects of Mathematics.